Efektivitas Metode Eksperimen Berbasis Mikroskopi Digital terhadap Keterampilan Proses Sains dan Psikomotorik Siswa pada Materi Protista - Akbar Rafi’i; Nisa Aulia Hafizah (Lembaga Publikasi Ilmiah Nusantara, 2026)
The study of Protista in senior high school biology requires direct observation of microscopic organisms. However, limited microscope operation skills and low levels of students' science process skills often hinder effective learning. This study aimed to evaluate the effectiveness of a digital microscopy-based experimental method in improving science process skills (SPS) and psychomotor skills in learning Protista, compare its effectiveness with conventional light microscopy, and analyze the statistical differences between the two instructional approaches. The research was conducted at a public senior high school in Ternate using a quasi-experimental pretest-posttest control group design. The participants consisted of 63 tenth-grade science students, with 32 students assigned to the experimental group and 31 students to the control group. Data were analyzed using the N-Gain index and an independent samples t-test. The experimental group achieved mean posttest scores of 74.28% for science process skills and 76.27% for psychomotor skills, with N-Gain values of 0.59 and 0.62, respectively, both categorized as moderate. These results were significantly higher than those of the control group, which obtained N-Gain values of 0.37 for science process skills and 0.39 for psychomotor skills. The independent samples t-test confirmed significant differences between the two groups for both variables (p < 0.001). These findings indicate that digital microscopy is more effective than conventional light microscopy in enhancing students' science process skills and psychomotor performance in learning Protista.